2011
DOI: 10.1063/1.3624943
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization in counter-rotating oscillators

Abstract: An oscillatory system can have opposite senses of rotation, clockwise or anticlockwise. We present a general mathematical description how to obtain counter-rotating oscillators from the definition of a dynamical system. A type of mixed synchronization emerges in counter-rotating oscillators under diffusive scalar coupling when complete synchronization and antisynchronization coexist in different state variables. We present numerical examples of limit cycle van der Pol oscillator and, chaotic Rössler and Lorenz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…In this case, the systems are termed corotating, while when the frequencies differ in sign, they are counter-rotating [47]. This latter situation is one of parameter mismatch, and in recent works [47,48,49], the characteristics of AD in such cases have been discussed; see also Sec. 4.…”
Section: Mismatched Oscillatorsmentioning
confidence: 99%
“…In this case, the systems are termed corotating, while when the frequencies differ in sign, they are counter-rotating [47]. This latter situation is one of parameter mismatch, and in recent works [47,48,49], the characteristics of AD in such cases have been discussed; see also Sec. 4.…”
Section: Mismatched Oscillatorsmentioning
confidence: 99%
“…The sense of a direction in the rotation of a trajectory of a dynamical system was first introduced by Tabor [17] which was elaborated further by Prasad [14]. A general rule how to change the direction of rotation in a dynamical system was proposed by the authors [9]. It was reported that, in two identical counterrotating oscillators, different pairs of state variables emerge into a mixed CS and antisynchronization(AS) state when a scalar coupling is introduced [9].…”
Section: Introductionmentioning
confidence: 99%
“…We focus on LS and PS scenario that demands more attention since it is more realistic in the larger coupling regime and has potential applications [3,9]. LS in chaotic systems has potential applications in the transmitting information in unidirectionally coupled oscillators [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noise induced effects may lead to interesting behavior for coupled oscillators, in particular, oppositely rotating coupled oscillators (see, for example, [20,21]). Our analysis could also be extended to include colored noise as discussed in [7].…”
mentioning
confidence: 99%